Milk-alkali syndrome: a 'quick ease' or a 'long-lasting problem'. (13th May 2020) - Wang, Mawson; Cho, Catherine; Gray, Callum; Chai, Thora Y; Daud, Ruhaida; Luttrell, Matthew
Abstract : Summary: We report the case of a 65-year-old female who presented with symptomatic hypercalcaemia (corrected calcium of 4.57 mmol/L) with confusion, myalgias and abdominal discomfort. She had a concomitant metabolic alkalosis (pH 7.46, HCO3 - 40 mmol/L, pCO2 54.6 mmHg). A history of significant Quick-Eze use (a calcium carbonate based antacid) for abdominal discomfort, for 2 weeks prior to presentation, suggested a diagnosis of milk-alkali syndrome (MAS). Further investigations did not demonstrate malignancy or primary hyperparathyroidism. Following management with i.v. fluid rehydration and a single dose of i.v. bisphosphonate, she developed symptomatic hypocalcaemia requiring oral and parenteral calcium replacement. She was discharged from the hospital with stable biochemistry on follow-up. This case demonstrates the importance of a detailed history in the diagnosis of severe hypercalcaemia, with MAS representing the third most common cause of hypercalcaemia. We discuss its pathophysiology and clinical importance, which can often present with severe hypercalcaemia that can respond precipitously to calcium-lowering therapy. Learning points: Milk-alkali syndrome is an often unrecognised cause for hypercalcaemia, but is the third most common cause of admission for hypercalcaemia. Calcium ingestion leading to MAS can occur at intakes as low as 1.0–1.5 g per day in those with risk factors. Early recognition of this syndrome can avoid the use of calcium-lowering therapy such as bisphosphonates which can precipitate hypocalcaemia.